IgE-mediated histamine release from nasal mucosa is inhibited by SLPI (secretory leukocyte protease inhibitor) to the level of spontaneous release. Issue 3 (1998) - Westin, U.; Lundberg, E.; Ohlsson, K.
Abstract : The secretory leukocyte protease inhibitor (SLPI) is a low-molecular-weight inhibitor of proteases, such as elastase and cathepsin G which are released from leukocytes during phagocytosis. The purpose of this study was to determine whether or not SLPI is able to inhibit IgE-mediated histamine release. Nasal mucosa from 11 test subjects without atopic disposition was used for this in vitro study. We found that SLPI inhibited histamine release in a dose-dependent way but was without influence on the spontaneous release.